Quelques aspects biochimiques et énergétiques aux principales espèces d’invertébrés benthiques du littoral roumain de la Mer Noire - Roșoiu, Natalia (Cercetări Marine - Recherches Marines, 2026)
The paper presents dynamics of water, mineral, total organic substance, protein, lipid and carbohydrate contents, as well as caloric values in some benthic invertebrates from the Black Sea. Significance of these compounds are pointed out with special references on their caloricity.